Geo‐hydromorphological assessment of Europe's southernmost blanket bogs. Issue 12 (8th July 2020) - Chico, G.; Clutterbuck, B.; Clough, J.; Lindsay, R.; Midgley, N.G.; Labadz, J.C.
Abstract: Blanket bogs are a globally rare type of ombrotrophic peatland internationally recognized for long‐term terrestrial carbon storage, the potential to serve as carbon sinks, habitat provision and for their palaeoenvironmental archive. This habitat is protected in the European Union under the Habitats Directive (92/43/EEC), but a number of blanket bogs located in the Cantabrian Mountains (northern Spain), representing the southernmost known edge‐of‐range for this habitat in Europe, are currently not recognized and are at increased threat of loss. Using climatic data, topography, aerial photography and peat depth surveys, this study has identified 10 new areas of blanket bog located between the administrative regions of Cantabria and Castilla y León. Peat depth data and topography were used to provide a detailed geomorphological description and hydromorphological classification (mesotope units) of these currently unrecognized areas of blanket bog. Maximum peat depth measured across the 10 sites ranged from 1.61 to 3.78 m, covering a total area of 18.6 ha of blanket bog (>40 cm peat depth). The volume of peat accumulated across the sites was determined to be more than 216 000 m 3 and is estimated to hold 19.89 ± 3.51 kt C. Twenty‐four individual hydrological mesotope units were described, indicating a diverse assemblage of blanket bogs in this region. The peatlands identified in this research extend the known limit of blanket bogs in Europe farther south than previously recorded and – combined with four other unprotected blanket bogs recently identified in the Cantabrian Mountains – these peatlands represent 10.5% of blanket bog currently recognized and protected in Spain. The range of anthropogenic pressures currently acting on peatlands in the Cantabrian Mountains indicates that without protection these important landforms and stored carbon may be lost. An urgent update of European peatland inventories is thus required to preserve these valuable carbon stores and potential carbon sinks. © 2020 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : This research identifies and provides geomorphological description, mesotope classification and carbon stored of 10 currently unrecognized areas of peatlands in northern Spain, extending the southernmost limit of blanket bogs in Europe. However, high anthropogenic pressures are affecting these blanket bogs and, without protection, these long‐term carbon stores and potential carbon sinks could disappear, removing a paleoenvironmental record of the last 8000 years.